Incidence of Asymptomatic Bacteriuria among Pregnant Women Attending Federal Medical Center, Katsina - Abdulkadir B.; Aisha A. S.; Abdulqadir I.; Abdulkarim B.; Binta S. A.; Ahmed Y. (UMYU Journal of Microbiology Research)
Asymptomatic bacteriuria is common among pregnant women and it is frequently associated with adverse pregnancy outcomes leading to maternal and fetal morbidity and mortality. The burden of asymptomatic bacteria in pregnancy has not been previously evaluated in this environment. Therefore, the study aimed to determine the prevalence of asymptomatic bacteriuria and its clinical correlate among pregnant women attending Federal Medical Center, Katsina. The study was a prospective study conducted among 126 antenatal attendees from 19th September – 4th November 2017. Urine microscopy and culture technique were conducted for each participant. The prevalence of asymptomatic bacteriuria among pregnant women was 19.8% and only gestational age and tribe had significant association with asymptomatic bacteriuria (p = 0.02) respectively however age (p = 0.66), educational status (p = 0.19) and settlement (p = 0.91) showed no significant association. Staphylococcus aureus was the most prevalent organism (40%), followed by coagulase negative Staphylococcus (32%) while Eschericia coli was least prevalent organism (4%). Asymptomatic bacteriuria is not uncommon among pregnant women in this environment; as such urine culture should be routinely carried out as part of antenatal care package for early detection and prevention of possible complications of urinary tract infections in pregnancy.